2023
DOI: 10.3389/fpsyg.2023.1076552
|View full text |Cite
|
Sign up to set email alerts
|

The effect of teacher support on Chinese university students’ sustainable online learning engagement and online academic persistence in the post-epidemic era

Abstract: Since entering the post-epidemic era of COVID-19 at the end of 2021, schools have mostly adopted a combined online and offline teaching mode to effectively respond to the normalized epidemic, which has changed the traditional learning mode of students. Based on the study demand-resources (SD-R) model theory, this study developed a research model and proposed six research hypotheses to explore the relationship between Chinese university students’ perceived teacher support (PTS), online academic self-efficacy (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…In addition, the researcher has reported its reliability at a suitable level. On the other hand, a review of the references of this article showed that many studies published in the field of online courses in the last two years had used this tool to measure academic engagement (202 articles posted on reputable sites, such as PubMed, tandfonline, and Springer) (55)(56)(57)(58)(59). Therefore, this tool was used in this research to provide a reliable tool to assess academic engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the researcher has reported its reliability at a suitable level. On the other hand, a review of the references of this article showed that many studies published in the field of online courses in the last two years had used this tool to measure academic engagement (202 articles posted on reputable sites, such as PubMed, tandfonline, and Springer) (55)(56)(57)(58)(59). Therefore, this tool was used in this research to provide a reliable tool to assess academic engagement.…”
Section: Discussionmentioning
confidence: 99%
“…These opportunities can manifest as training, learning experiences, and support for growth. When students perceive greater study opportunities, they expand their learning horizons and actively engage in acquiring valuable knowledge and skills provided by teachers, thereby promoting their study engagement (Guskey, 2002;Ma et al, 2023). Students with limited study opportunities may experience reduced confidence in their academic abilities due to a lack of sufficient support or access to a variety of study opportunities, which can influence their level of study engagement to some extent (Kelly et al, 2021).…”
Section: Relation Between Teacher Support and Study Engagement And St...mentioning
confidence: 99%
“…Relevant studies have highlighted the significant impact of teacher support on college students' mental health. Additionally, other study-related factors such as peer support, academic self-efficacy, and study opportunities are closely associated with students' mental well-being (Hitches et al, 2022;Ma et al, 2023;. Based on the SD-R model theory, the level of teacher support directly or indirectly affects students'mental health.…”
Section: Introductionmentioning
confidence: 99%
“…This emphasis on practicality is particularly significant for student teachers who are entrusted with the responsibility of translating their acquired skills and knowledge into effective teaching methods. Within educational contexts, the concept of -learning efficacy‖ assumes a critical role, referring to individuals' capacity to both acquire and apply knowledge and skills (Libii, 2007;Ma et al, 2023;Schunk & Ertmer, 2000). A higher level of learning efficiency signifies effective learning and application, indicating that individuals can achieve desired learning outcomes with greater effectiveness.…”
Section: Introductionmentioning
confidence: 99%